The narrative structure and antiwar discourse of Born on the Fourth of July: Screenplay and film. (1st May 2013) - Larson, Stephen
This article examines the atypical narrative structure director Oliver Stone and co-scenarist Ron Kovic employed to create a screenplay and cinematic incarnation of the latter's memoir, Born on the Fourth of July (Kovic, 1976). The eponymous film (Stone, 1989) is exceptional from other screen war biographies in that it adeptly incorporates a triptych and elongated five-act structure to punctuate the transformation of a gung-ho marine into a committed political activist. The article's main purpose is to expand on the foundations of narrative theory that have been applied to Fourth of July and create a new perceptual lens (via Freytagian criticism) for other avenues to examine how the text cultivates an antiwar discourse. Stone's structural choices are motivated by a political agenda. It is argued that via the theoretical application of Gustav Freytag's pyramidal five-act structure to Fourth of July's narratological makeup, I demonstrate how Stone presents a series of significant signs and signifiers through several scenes which effectively depict Kovic's evolving maturation and growth. Although Freytag's pyramid has historically played an important role in the analysis of modes such as drama and film, I propose to bring it to bear on Stone's film in order to reframe existing critical and popular discussions of the film.